2023
DOI: 10.1101/2023.07.28.23293330
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identifying proteomic risk factors for cancer using prospective and exome analyses: 1,463 circulating proteins and risk of 19 cancers in the UK Biobank

Abstract: Background Proteins are essential for the development and progression of cancer and for the human body's defense against tumor onset. The availability of a large panel of protein measurements and whole exome sequence data in the UK Biobank has enabled the simultaneous examination of plasma protein associations with risk across multiple cancer sites and their potential role in cancer etiology. Methods We investigated the associations of plasma proteins with incidence of 19 cancers and 9 cancer subsites in up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…We searched the literature for proteins which were assessed pre-diagnostically of glioma. Our search identified EGFR and GFAP (33,34). Increased circulating levels of EGFR was associated with glioblastoma risk (33), and increased levels of GFAP were associated with brain cancer risk (34), both of which were assessed before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We searched the literature for proteins which were assessed pre-diagnostically of glioma. Our search identified EGFR and GFAP (33,34). Increased circulating levels of EGFR was associated with glioblastoma risk (33), and increased levels of GFAP were associated with brain cancer risk (34), both of which were assessed before diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our search identified EGFR and GFAP (33,34). Increased circulating levels of EGFR was associated with glioblastoma risk (33), and increased levels of GFAP were associated with brain cancer risk (34), both of which were assessed before diagnosis. Similarly, in our study we identified reverse MR associations usually found increased circulating EGFR and GFAP in reverse MR associated with glioma, glioblastoma and non-glioblastoma analysis compared to the forward MR analysis (Table 3-4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 60 61 Thus, we will compare the strength and direction of SNP-protein associations among cancer cases, participants without a cancer diagnosis and in samples broadly representative of the general population in UK Biobank. 62 We will perform these analyses for UK Biobank cancer cases pooled across the seven cancer sites which our analyses focus on (n=3375), each of the seven cancer sites individually ( table 4 ), and pooled across all cancer sites. 62 …”
Section: Methods and Analysismentioning
confidence: 99%
“… 62 We will perform these analyses for UK Biobank cancer cases pooled across the seven cancer sites which our analyses focus on (n=3375), each of the seven cancer sites individually ( table 4 ), and pooled across all cancer sites. 62 …”
Section: Methods and Analysismentioning
confidence: 99%